The Health Effects of Universal Early Childhood Interventions: Evidence from Sure Start - Sarah Cattan; Gabriella Conti; Christine Farquharson; Rita Ginja; Maud Pecher (Institute of Labor Economics (IZA), 2021)
We evaluate the short- and medium-term health impacts of Sure Start, a large-scale and universal early childhood program in England. We exploit the rollout of the program and implement a difference-in-difference approach, combining data on the exact location and opening date of Sure Start centers with administrative data on the universe of admissions to public-sector hospitals. Exposure to an additional Sure Start center per thousand age-eligible children increases hospitalization by 10% at age 1 (around 6,700 hospitalizations per year), but reduces them by 8-9% across ages 11 to 15 (around 13,150 hospitalizations per year). These findings show that early childhood programs that are less intensive than small-scale 'model programs' can deliver significant health benefits, even in contexts with universal healthcare. Impacts are driven by hospitalizations for preventable conditions and are concentrated in disadvantaged areas, suggesting that enriching early childhood environments might be a successful strategy to reduce inequalities in health.
Keywords: I10; I14; I18; 330; health; early childhood intervention; difference-in-difference